Investigates the performance of office reits in Malaysia focusing on pandemic (2020-2021), and post pandemic (2022-2023) periods - Lim, Chee Choon (2025)
This thesis examines the performance of office Real Estate Investment Trusts (REITs) in Malaysia during the COVID-19 pandemic (2020-2021) and the post-pandemic recovery period (2022-2023). The study utilizes key financial metrics, including the Sharpe Ratio, Treynor Ratio, Jensen Alpha, R-Squared, and Risk Diversifiability, to evaluate the risk-adjusted returns, market sensitivity, and overall performance of office REITs across these two periods. The research aims to assess how office REITs adapted to market disruptions caused by the pandemic and how they have performed in the recovery phase.